1997
DOI: 10.1006/cbir.1996.0110
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic Cells From Rat Long Bone Ii: Adhesion to Substrata and Integrin Expression in Primary and Propagated Cultures

Abstract: Propagation in vitro of rat tibial osteoblasts (ROB) is accompanied by increased expression of the early osteogenic marker alkaline phosphatase (AP) and maturation of the osteogenic phenotype. In order to establish the pattern of the integrin expressed in ROB during progression to the mature osteoblastic phenotype, we have used biosynthetic, immunoblotting and immunohistochemical assays. We immunoprecipitated from osteoblasts, expanded for 1.5- and 7.5-doubling, alpha 5 beta 1, alpha v beta 3, alpha 3 beta 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Osteoblasts generally express integrin subunits a 1 , a 2 , a 3 , a 4 , a 5 , a 6 , a V , b 1 , b 3 , and b 5 on various substrates [24]. For attachment to fibronectin and collagen type I, osteoblasts express integrin subunit b 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts generally express integrin subunits a 1 , a 2 , a 3 , a 4 , a 5 , a 6 , a V , b 1 , b 3 , and b 5 on various substrates [24]. For attachment to fibronectin and collagen type I, osteoblasts express integrin subunit b 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha subunit expression data have been more inconsistent, with different combinations of α1, α2, α3, α4, α5, and αv subunits having been detected by immunohistochemistry in human and rat bone 30–34. The expression of the previously mentioned alpha subunits has also variously been determined by flow cytometry, immunoprecipitation, immunocytochemistry, and Northern blot analysis on primary bone cultures 29–31, 35–39. Although reports of alpha subunit and integrin heterodimer expression in osteoblasts have sometimes been contradictory, many studies have identified the α1β1, α2β1, α3β1, α5β1, αvβ3 integrins, and their subunits in osteoblasts and bone cultures 29, 33, 37, 38.…”
Section: Bone Ecm Composition and Key Integrins Implicated In Osteogementioning
confidence: 99%
“…Changes ensuing from ECM proteolysis elicit cellular responses through integrin and nonintegrin receptors (56,61,70–72) and, in turn, integrin occupancy can affect differentiation and MMP expression (59,62,63) . During osteogenesis, the modulation of synthesis and deposition of the ECM and of the associated endogenous growth factors and cytokines change the osteoblast microenvironment.…”
Section: Introductionmentioning
confidence: 99%